Sinalização do hormônio tireoideano no cérebro de camundongos após status epilepticus induzido por Pilocarpina - Nascimento, Bruna Pascarelli Pedrico do [UNIFESP] (2016)
Thyroid hormones play an important role in the development and maintenance of Central Nervous System through the control of gene expression. Although serum concentration of TH is remarkably stable, deiodinases regulate their signaling in a precise spatio- and temporal-manner by controlling the activation and inactivation of TH. Deiodinases expression and activity can change in critically ill patients, changing T3 signaling in tissues. Status epilepticus is a well-known central nervous system insult that leads to the development of Temporal Lobe Epilepsy, and can be defined as a state of continuous seizure activity or two or more sequential seizures without full recovery of consciousness between seizures. Seeing that various abnormalities frequently occur during seizures, we assume that this condition may lead to changes in deiodinases expression and activity in some brain regions, leading to local changes in T3 levels and, consequently, to changes in brain metabolism. Thus, we have studied whether seizures cause changes in deiodinases expression and in T3 signaling in mouse brain following status epilepticus, as well as the role of D2 in these changes. To that, C57Bl/J6, CRE GFAP and AstroD2KO mice were subjected to pilocarpine/lithium-pilocarpine model of epilepsy and Dio2 and Dio3, as well as the T3-regulated genes mRNA levels in the brain were analyzed by real-time PCR. We also analyzed the enzymatic activity of D2 and D3 and HIF-1α and D3 expression in hippocampus. TSH, T3 and T4 serum levels were also measured. Notably, status epilepticus causes a decrease in thyroid hormones serum levels, an increase in expression and activity of D2 and a decrease in Dio3 expression in mouse brain. These changes resulted in moderate variation in the expression of T3-regulated genes, suggesting that seizures change T3 signaling in mouse brain.